Wawasan Al-Qur’an tentang Media Komunikasi dan Informasi - Asep Usman Ismail (Jurnal Lektur Keagamaan, 2012)
Media is one of the most important element in communication. In the perspective of Qur’an, there are two forms of primary communication media, Oral Language which is verbal communication and Sign Language which is non-verbal communication. Besides, there are two supporting communication media, Friday Speech and Murasalat or Correspondence. In two forms of communication media, primary communication media and supporting communication media, Al-Qur’an emphasizes to the moslem to communicate effectively and efficiently, so that their communication is qualified with choosing a good diction so that the message is sticked on the mind of the communicated person. At last, the communication can change and bring the communicated person to the religion of Allah swt